Novas soluções de buracos negros regulares com fontes de matéria quase-localizadas em 2+1 dimensões - Santos, Alana Carolina Lima dos (2023)
The solutions to Einstein’s field equations describe many astrophysics elements, including the dynamics of the universe in Cosmology. Nonetheless, some spherically symmetrical solutions, when considered in a vacuum, are not valids in r = 0, due to the found disagreements. In this sense, James Bardeen was the first to propose modifications on the metric to avoid this incompatibility, on the called Regular Black Holes. Posteriorly, this change in the description was associated with nonlinear electrodynamics. In this sense, after a brief revision of the general relativity’s solutions, we investigated the generalized solution Bardeen’s with the inclusion of a new matter source given by the Quintessence - a scalar field proposed like a model to dark energy. Following, guided by Yun He and Meng-Sen approachs, we find general relations which permit identify densities arises from perfect fluids to nonlinear electrodynamics, analyzing the mapping consistency through the limit of Maxwell’s Classical Electromagnetism. Posteriorly, generalizating the quasi-localized matter density model defined by Estrada and Tello-Ortiz, we find new solutions of regular black holes and study the energy conditions. Finally, we discuss the thermodynamic analysis of these new solutions.